Use of topical bromfenac for treating ocular pain and inflammation beyond cataract surgery: a review of published studies - Schechter BA (Dove Medical Press, 2019)
Barry A SchechterCornea and Cataract Service, Florida Eye Microsurgical Institute, Boynton Beach, FL, USAAbstract: Topical ophthalmic nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used to treat postoperative inflammation and pain following cataract surgery and for treatment and prophylaxis of pseudophakic cystoid macular edema (CME). Bromfenac is a brominated NSAID with strong in vitro anti-inflammatory potency. Like other ophthalmic NSAIDs, bromfenac is often used outside of the cataract surgery setting. This paper provides an overview of bromfenac’s preclinical ocular pharmacology and pharmacokinetics, followed by a review of 23 published clinical studies in which various marketed bromfenac formulations were used for conditions other than cataract surgery or pseudophakic CME. These include: post-refractive eye surgery; macular edema associated with diabetes, uveitis, or retinal vein occlusion; inflammation associated with age-related macular degeneration; pain related to intravitreal injections; and other ocular anterior segment and surface disorders with an inflammatory component. The published evidence reviewed supports the safety and effectiveness of bromfenac in these additional ophthalmic indications. Bromfenac was well tolerated when given alone or in combination with intravitreal anti-vascular endothelial growth factor agents, topical corticosteroids, or topical mast-cell stabilizers. The most common adverse event reported was ocular irritation. No serious adverse events (ie, corneal epithelial disorders) were reported, although the majority of studies did not systematically evaluate potential side effects. Corneal complications, such as melts reported with diclofenac and ketorolac, were not observed with bromfenac in the studies. In summary, published study data support the clinical utility of bromfenac in various ocular disorders beyond post-cataract surgery. Additional studies are warranted to further define the potential role of bromfenac ophthalmic solution in clinical practice.Keywords: bromfenac, clinical studies, ocular inflammation, pain, safety